Sex-related differences in incidence, phenotype and risk of sudden cardiac death in inherited arrhythmia syndromes - Asatryan, Babken; Barth, Andreas S. (Frontiers in Cardiovascular Medicine, 2023)
Inherited Arrhythmia Syndromes (IAS) including long QT and Brugada Syndrome, are characterized by life-threatening arrhythmias in the absence of structural heart disease and are caused by pathogenic variants in genes encoding cardiac ion channels or associated proteins. Studies of large pedigrees of families affected by IAS have demonstrated incomplete penetrance and variable expressivity. Biological sex is one of several factors that has been recognized to modulate disease severity in IAS. There is a growing body of evidence linking sex hormones to the susceptibility to arrhythmias, yet, many sex-specific disease aspects remain underrecognized as findings from cohort studies are often generalized to both sexes without considering relevant sex-related differences in prevalence and outcome. In this review, we highlight current knowledge of sex-specific variations in normal cardiac electrophysiology and susceptibility to arrhythmias in IAS.